Test weight affects the milling characteristics of grain sorghum - S L Traylor; Timothy J Herrman; Keith C Behnke; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 1995)
As test weight was reduced from normal to intermediate (i.e., from 58 to 52 lb/bu), little change occurred in milling characteristics of grain sorghum. However, as test weight was decreased from intermediate to light (52 to 39 lb/bu), production rate slowed and cost of grinding increased dramatically. Decreasing screen opening size from 8/64 in to 3/64 in also decreased production rates and increased electrical energy costs, with these effects much more pronounced in light test-weight sorghum.; Swine Day, Manhattan, KS, November 16, 1995
Keywords: Swine day; 1995; Kansas Agricultural Experiment Station contribution; no. 96-140-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 746; Swine; Sorghum; Test weight; Grinding